Esophageal perforations secondary to endoscopic procededures (report of three cases) - Ahmet TEZEL,; Tülin ŞAHİN,; Yasemin KOŞAR,; Dilek OĞUZ,; Kemal ARDA,; Burhan ŞAHİN,; Turhan CUMHUR, (Turkish Journal of Gastroenterology, 2019)
-